2007
DOI: 10.1128/iai.00716-06
|View full text |Cite
|
Sign up to set email alerts
|

The YfgL Lipoprotein Is Essential for Type III Secretion System Expression and Virulence of Salmonella enterica Serovar Enteritidis

Abstract: Salmonella enterica, like many gram-negative pathogens, uses type three secretion systems (TTSS) to infect its hosts. The three TTSS of Salmonella, namely, TTSS-1, TTSS-2, and flagella, play a major role in the virulence of this bacterium, allowing it to cross the intestinal barrier and to disseminate systemically. Previous data from our laboratory have demonstrated the involvement of the chromosomal region harboring the yfgL, engA, and yfgJ open reading frames in S. enterica serovar Enteritidis virulence. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 57 publications
1
64
0
Order By: Relevance
“…26,27 , 34 In S. enterica serovar Enteritidis, the yfgL mutant had reduced invasivity for enterocytes compared to the wild-type strain. 34 Similarly, deletion of the yfgL gene in an adherent-invasive E. coli strain LF82 resulted in a decreased invasivity for intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26,27 , 34 In S. enterica serovar Enteritidis, the yfgL mutant had reduced invasivity for enterocytes compared to the wild-type strain. 34 Similarly, deletion of the yfgL gene in an adherent-invasive E. coli strain LF82 resulted in a decreased invasivity for intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…22,24,25 YfgL (BamB) is an OM lipoprotein, which is anchored to the periplasmic face of the OM 22 and displays a role in membrane permeability and antibiotic resistance of E. coli and S. enterica serovar Enteritidis. 26,27 A previous study demonstrated that the Salmonella YfgL lipoprotein is essential for expression of the type-III secretion system. 27 Several putative secretion systems, but not a type-III secretion system, have already been identified in the K. pneumoniae NTUH-K2044 genome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the genes encoding secretory effector proteins or genes that regulate their expression lead to virulence attenuation in S. Enteritidis (Amy et al, 2004;Fardini et al, 2007;Parker & GuardPetter, 2001). At least two low invasive isolates, C19 and C45, tested here showed impaired secretion of SipA and SipD proteins (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…GFP-Cdc42 was generated by subcloning wild-type Cdc42 from pRK5-myc Cdc42 into pEGFP-C2 (CLONTECH Laboratories Inc; BamHI and EcoRI restriction sites). The rck mutant of LA5 strain was obtained using the lambda-Red mutagenesis system, modified as previously described [43,44]. The sequences of P1 and P2 primers used for this strain construction are listed in Table 3.…”
Section: Dna Constructsmentioning
confidence: 99%